1999
DOI: 10.21273/jashs.124.1.46
|View full text |Cite
|
Sign up to set email alerts
|

Cool Orchard Temperatures or Growing Trees in Containers Can Inhibit Leaf Gas Exchange of Avocado and Mango

Abstract: Leaf gas exchange of avocado (Persea americana Mill.) and mango (Mangifera indica L.) trees in containers and in an orchard (field-grown trees) was measured over a range of photosynthetic photon fluxes (PPF) and ambient CO2 concentrations (Ca). Net CO2 assimilation (A) and intercellular partial pressure of CO2 ( Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0
6

Year Published

1999
1999
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(26 citation statements)
references
References 26 publications
2
16
0
6
Order By: Relevance
“…A strong correlation between high starch concentration in leaves and low assimilation rate can generally be found (Paul and Foyer 2001). Whiley et al (1999) observed that A max was substantially lower in leaves of mango trees grown in containers than in field-grown trees. They attributed this decrease in photosynthesis to end-product inhibition by carbohydrate accumulation.…”
Section: Relationship Between Nitrogen and Leaf Carbohydrate Concentrmentioning
confidence: 96%
“…A strong correlation between high starch concentration in leaves and low assimilation rate can generally be found (Paul and Foyer 2001). Whiley et al (1999) observed that A max was substantially lower in leaves of mango trees grown in containers than in field-grown trees. They attributed this decrease in photosynthesis to end-product inhibition by carbohydrate accumulation.…”
Section: Relationship Between Nitrogen and Leaf Carbohydrate Concentrmentioning
confidence: 96%
“…The subtropical avocado and mango have been reported to have low photosynthetic rates, but improved rates were recently obtained under optimal conditions Whiley and Schaffer, 1994). Whiley et al (1999) suggest that orchard trees may frequently be suffering from root restriction, which limits their photosynthetic capacity. Similar views have been expressed with regard to citrus by Idso and Kimball (1994).…”
Section: The Evergreen Frameworkmentioning
confidence: 99%
“…Several studies have shown a feedback inhibition of A through leaf carbohydrate accumulation, imposed by restricted rooting volume because of small pot size (e.g. Robbins and Pharr 1988;Thomas and Strain 1991;Whiley et al 1999). In a few studies, however, A was apparently unresponsive to (Krizek et al 1985; Barrett and Gifford 1995), or increased with (Carmi et al 1983), decreasing pot size.…”
Section: Introductionmentioning
confidence: 99%